2006
DOI: 10.1038/sj.ijo.0803250
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of excess body weight and health-related quality of life: evidence from a population study in Taiwan

Abstract: Objective: Excess body weight is related to significant morbidity and mortality. However, less is known about the relationship of body weight to health-related quality of life (HRQOL), especially for Asian populations. We examined the relationship of excess weight and HRQOL in a general population sample from Taiwan. Research methods and procedures: This cross-sectional study used a national representative sample (n ¼ 14 221) from the 2001 Taiwan National Health Interview Survey. Body weight was categorized us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
126
6
12

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(173 citation statements)
references
References 59 publications
29
126
6
12
Order By: Relevance
“…Numerous cross-sectional studies have affirmed that compared to normal-weight individuals, obese individuals are more likely to have a poorer level of physical HRQoL [8][9][10][11][12][13][14][15][16][17]22,25,30,31,34,37]. Our study results confirmed that BMI is inversely associated with physical SF-12 summary score.…”
Section: Cross-sectional Association Between Bmi and Hrqolsupporting
confidence: 81%
See 1 more Smart Citation
“…Numerous cross-sectional studies have affirmed that compared to normal-weight individuals, obese individuals are more likely to have a poorer level of physical HRQoL [8][9][10][11][12][13][14][15][16][17]22,25,30,31,34,37]. Our study results confirmed that BMI is inversely associated with physical SF-12 summary score.…”
Section: Cross-sectional Association Between Bmi and Hrqolsupporting
confidence: 81%
“…In overweight and obese individuals, the physical SF-12 summary score decreased with increasing BMI whereas no such association was found in normalweight individuals. Several studies identified the highest levels of physical HRQoL among normal-weight adults [8][9][10][11]13,16,17,30,54]. However, other studies showed significantly poorer physical HRQoL only in obese but not in overweight individuals [14,15,31,37].…”
Section: Cross-sectional Association Between Bmi and Hrqolmentioning
confidence: 97%
“…Hallamos menor índice total y dominio personal de CV en los hombres con ligero sobrepeso, respecto a los de peso cercano al correcto, lo que difiere de un estudio hecho en Canadá 39 con 6.302 mujeres y 2.792 hombres mayores de 25 años que encontró que la CV fue ligeramente mejor, incluso para los hombres con ligero sobrepeso, respecto a los de peso normal y de otro estudio que encontró que los hombres con sobrepeso tenían mejores puntuaciones en los dominios mentales que los de peso normal 40 . Probablemente, en esos estudios donde la edad fue mayor en los hombres se observó una menor preocupación por la apariencia personal que en los adolescentes, como en nuestro estudio, donde su apariencia es aún un aspecto importante de su vida interior.…”
Section: Grupos/calidad De Vidaunclassified
“…Na podstawie badań antropometrycznych podzielono pacjentki na dwie grupy: grupę A (n = 16), którą stanowiły pacjentki z otłuszczeniem pośladkowo-udowym -typu "gruszka" (WHR 0,74 ±0,12), i grupę B (n = 16), którą tworzyły kobiety z brzusznym typem otłuszczenia -typu "jabłko" (WHR 0,93 ±0,14). W badaniu jakości życia wykorzystano Kwestionariusz ogólnego stanu zdrowia Davida Goldberga (GHQ-12 Goldberga), dostosowany kulturowo.…”
Section: Streszczenieunclassified
“…Aż 89% kobiet z tej grupy wykazywało pogorszenie samopoczucia w ciągu ostatnich tygodni. W piśmiennictwie jest wiele danych na temat zależności pomiędzy jakością życia a wartością BMI u kobiet i mężczyzn w różnych kategoriach wiekowych, w tym także kobiet powyżej 50. roku życia [10][11][12][13][14][15][16][17][18][19][20][21]. We wszystkich wspomnianych badaniach znaleziono istotną zależność pomiędzy wartością BMI a jakością życia, niezależnie od użytego do badań kwestionariusza.…”
Section: Whr -Stosunek Obwodu Talii Do Obwodu Bioder (Waist To Hip Raunclassified